Psalidodon endy - Alonso, Felipe (2022)
Psalidodon endy has most recently been assessed for The IUCN Red List of Threatened Species in 2020. Psalidodon endy is listed as Vulnerable under criteria B1ab(iii)+2ab(iii); D2.